2001
DOI: 10.1159/000064638
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression but Not Genetic Alteration of <i>BRG1</i>, a Component of the SWI/SNF Complex, Is Associated with the Advanced Stage of Human Gastric Carcinomas

Abstract: BRG1, a component of the SWI/SNF complex, regulates gene transcription through chromatin remodeling. Certain human cancer cell lines have been shown to contain homozygous deletions or mutations, half of which are concentrated in exons 4 and 10, resulting in aberrant BRG1 expression. We examined the expression of BRG1 in 38 gastric carcinomas and corresponding nonneoplastic mucosa by using the quantitative real-time RT-PCR method. Twenty-three carcinomas (61%) showed increased BRG1 expression in tumor tissue in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
46
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 23 publications
12
46
1
Order By: Relevance
“…We previously reported that BRG1, a component of the SWI/SNF complex, is not mutated in gastric carcinoma. 38) In the present study, we found that in 50% of gastric carcinoma tissues, the 5′ CpG island of the HLTF gene was methylated, and this methylation was associated with reduced expression. In the gastric carcinoma cell lines, DNA methylation of HLTF was detected in KATO-III cells, which did not appear to express HLTF mRNA.…”
Section: Discussionsupporting
confidence: 49%
“…We previously reported that BRG1, a component of the SWI/SNF complex, is not mutated in gastric carcinoma. 38) In the present study, we found that in 50% of gastric carcinoma tissues, the 5′ CpG island of the HLTF gene was methylated, and this methylation was associated with reduced expression. In the gastric carcinoma cell lines, DNA methylation of HLTF was detected in KATO-III cells, which did not appear to express HLTF mRNA.…”
Section: Discussionsupporting
confidence: 49%
“…In fact, BRG1 may act in an oncogenic manner in some tumors (Wang et al, 2009). Furthermore, increased expression of BRG1 has been associated with tumor growth and invasiveness in prostate tumors (Sun et al, 2007) as well as higher metastatic behavior in gastric carcinomas (Sentani et al, 2001). Although brg1 heterozygotes have higher incidence of tumors, it is worth noting that these are mostly differentiated epithelial tumors (Bultman et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Although loss of BRG1 and/or BRM-the two mutually exclusive ATPase subunits of the SWI/SNF chromatin-remodeling complex-is found in a number of cancer lines and primary tumors (Reisman et al, 2009), expression of BRG1, but not of BRM, has also been correlated with higher invasive/metastatic behavior in carcinomas (Sentani et al, 2001;Sun et al, 2007). BRG1 associates with DNA-binding transcription factors and histone-modifying enzymes to activate/repress transcription as well as to regulate DNA replication, repair and recombination (Trotter and Archer, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this group also examined primary lung tumors with loss of heterozygosity in the BRG1 locus and did not find any appreciable mutations in these tumors (Medina et al, 2004). Sentani et al (2001) found no BRG1 mutations in 8 gastric carcinoma cell lines and 33 primary gastric carcinomas. Likewise, Valdman et al (2003) reported no somatic mutations in any of the 35 BRG1 exons in samples from 21 prostate cancer patients.…”
Section: Loss Of Heterozygosity Occurs At the Brg1 And Brm Locimentioning
confidence: 94%